Early weaning in pigeons (Columba Livia domestica): effects on squabs performance and reproductive performance of parents - Omar A. Mohamed; Ibrahim M. Khattab; Mohammad A. Elsagheer (BMC Veterinary Research)
Abstract Background Artificial hatching and early artificial feeding of squabs can potentially reduce pigeon rearing costs, shorten breeding cycles, and enhance overall productivity. Two experiments were conducted to evaluate the effect of early weaning on growth performance, feed consumption, parents’ reproductive performance, and egg traits. Methods In Experiment 1, A total of 300 pairs of adult White Mirthys pigeons were randomly divided into three groups: W28, W7, and W0. These groups represent pigeons separated from their squabs at different ages: 28 days, 7 days, and 0 days (at hatch), respectively. Each group consisted of ten replicates, with each replicate comprising ten pairs of pigeons. In experiment 2, a total of 566 White Mirthys pigeon squabs were randomly assigned to three treatment groups: W28, W7, and W0. These groups represent squabs separated from their parents at different ages: 28 days, 7 days, and 0 days (at hatch), respectively. Results The results indicated that early weaning of squabs significantly decreased body weight, weight gain, feed intake, and feed conversion ratio (P < 0.05), while also increasing the mortality rate in the W0 group compared to the W28 and W7 groups. There were no significant differences in body weight, weight gain, or mortality rate between the W28 and W7 groups. Pigeons in the W0 group exhibited significantly lower (P < 0.001) egg-laying cycle and reproductive cycle. Still, they produced more eggs laid and weaned squabs than the W28 and W7 groups. Early weaning had no significant impact on hatchability rate (P = 0.220), egg weight (P = 0.580), egg length (P = 0.308), egg width (P = 0.488), or egg shape index (P = 0.167). However, the eggs from the early weaning group (W0) had a lower shell thickness (P = 0.002) compared to the control (W28) and W7 groups. Conclusions Early weaning at hatching has been found to reduce the growth performance of squabs; however, it significantly enhances the reproductive performance of parent pigeons. This method presents a promising strategy for increasing the reproductive rate of parent pigeons and boosting the annual production of squabs.